Confirming university students’ individual reading habit on academic text - Herman Resyadi; Dea Serly Safitri; Darmawati Fitriansyah (International Journal of Research on English Teaching and Applied Linguistics, 2021)
The main concern of this research was aimed at confirming the students’ individual readinghabit on academic text. It was navigated by online descriptive survey which involved 31students of English Education program. The data were collected through online questionnaireon WhatsApp Group Discussion by considering under the Covid19 situation and analyzed byusing SPSS. The result exposed (1) that the students have positive feeling on academic text,(2) most of the students read academic text at least once a week, (3) Academic book is themost types of academic text read by the students, (4) Busy with assignments becomes themain reason why the students not reading academic text. This research confirmed that thestudents have sufficient reading habit on academic text.